5x-24+3x+36=35+6x-2

Simple and best practice solution for 5x-24+3x+36=35+6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-24+3x+36=35+6x-2 equation:


Simplifying
5x + -24 + 3x + 36 = 35 + 6x + -2

Reorder the terms:
-24 + 36 + 5x + 3x = 35 + 6x + -2

Combine like terms: -24 + 36 = 12
12 + 5x + 3x = 35 + 6x + -2

Combine like terms: 5x + 3x = 8x
12 + 8x = 35 + 6x + -2

Reorder the terms:
12 + 8x = 35 + -2 + 6x

Combine like terms: 35 + -2 = 33
12 + 8x = 33 + 6x

Solving
12 + 8x = 33 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
12 + 8x + -6x = 33 + 6x + -6x

Combine like terms: 8x + -6x = 2x
12 + 2x = 33 + 6x + -6x

Combine like terms: 6x + -6x = 0
12 + 2x = 33 + 0
12 + 2x = 33

Add '-12' to each side of the equation.
12 + -12 + 2x = 33 + -12

Combine like terms: 12 + -12 = 0
0 + 2x = 33 + -12
2x = 33 + -12

Combine like terms: 33 + -12 = 21
2x = 21

Divide each side by '2'.
x = 10.5

Simplifying
x = 10.5

See similar equations:

| 2x+5y=17-4x | | 18=v+20 | | 9c+10=100 | | U/3-7=-2 | | N+(n+2)+(n+4)=171 | | 6m^2+7x=5 | | 7X-4X+3=2X-8 | | 7(9b+6)= | | y+4x=14 | | (3-2x)=14 | | 6x-16=16-2x | | 5x+2(x-6)=4(x+1)-3 | | 2x+4=10+5 | | 9n=536 | | 7=2+t | | 8x+40=90 | | -9(6f-3)= | | 13c-90=5c-34 | | 8/24=6/n | | 7.6(x-2.25)=-15.2 | | 6(10-5x)=45-5(5x+1) | | 64x^2+16x=1 | | 5m-20=4m+16 | | -9(7y-2)= | | 2-3a=8-2(2a+7) | | 2x+3+(2y-2)yi=0 | | 20=2w+4 | | 5.2(x-2.25)=-20.4 | | 18=2h-4 | | 54=-9a | | 4z+2=6z | | 12x^2+2x=5 |

Equations solver categories